Visible-spectrum gaze tracking for sports - Pires, B. R.; Hwangbo, M.; Devyver, M.; Kanade, T. (IEEE/CVF Conference on Computer Vision and Pattern Recognition, 2013)
In sports, wearable gaze tracking devices can enrich the viewer experience and be a powerful training tool. Because devices can be used for long periods of time, often outside, it is desirable that they do not use active illumination (infra-red light sources) for safety reasons and to minimize the interference of the sun. Unlike traditional wearable devices, in sports, the gaze tracking method must be robust to (often dramatic) movements of the user in relation to the device (i.e. the common assumption that, because the device is wearable, the eye does not move with regards to the camera no longer holds.) This paper extends a visiblespectrum gaze tracker in the literature to handle the requirements of a motor-sports application. Specifically, the method presented removes the original assumption (in the original method) that the eye position is fixed, and proposes the use of template matching to allow for changes in the eye location from frame to frame. Experimental results demonstrate that the proposed method can handle severe changes in the eye location and is very fast to compute (up to 60 frames per second in modern hardware.)